Defining Pistorius - Amanda K. Booher (Disability Studies Quarterly, 2011)
In 2008, the International Association of Athletics Federation (IAAF) defined Oscar Pistorius, a South African sprinter with double transtibial amputations, as both disabled and superabled in the course of his attempt to qualify for the Beijing Olympics. This paper examines the grounds for and effects of the constructed definitions of "disabled," "abled," "superabled," and "normal" through explication of the documents and pronouncements of the IAAF, as well as those in Pistorius' appeal to the Court of Arbitration for Sport. While the explication demonstrates the power of definition in Pistorius’ case, this paper argues for greater specificity and malleability in definition construction in relation to bodies and technologies/prosthetics.
Keywords: Ability; definition; disability; Foucault; Olympics; Pistorius; prosthetics